Plasty of the stenosed terminal sygmostoma, using the rotated flap - O. I. Tkachenko; V. E. Maksymovskyj; V. V. Pyrogov (Клінічна хірургія)
Plasty of the stenosed terminal sygmostoma, using the rotated flap